Studi Mitigasi Covid-19 Bagi Mayarakat Nelayan Desa Sungai Kayu Ara Kabupaten Siak Provinsi Riau - Puspita Fitriansyah; Darwis; Viktor Amrifo (Jurusan Sosial Ekonomi Perikanan, 2022)
This study aims to identify structural and non-structural mitigation in Sungai Kayu Ara Village. This research was conducted in March 2021 in Sungai Kayu Ara Village, Sungai Apit District, Siak Regency, Riau Province. The purpose of this study was to determine the mitigation policies of fishermen households in Sungai Kayu Ara Village due to social engineering of the COVID-19 pandemic. The method used in this study using the Survey Method. The population in this study were fishing households totaling 48 households. The technique of determining respondents is by means of a census, which is taking the entire population as respondents. Data collection is done by means of observation, in-depth interviews, documentation, literature study, and searching data and information online. Analysis of the data used are: qualitative descriptive analysis. Structural and non-structural Covid-19 mitigation in Sungai Kayu Ara Village, Sungai Apit District, Siak Regency focuses more on implementing government policies stipulated through the Regent's Regulation on Handling Infectious Diseases and the Regent's Regulation on the Implementation of Administrative Sanctions for Enforcement. health protocols in handling infectious diseases. Structural and non-structural mitigation of Covid-19 carried out by fishing households in the research location is the 3M health protocol policy, namely wearing masks, maintaining distance and avoiding crowds, and washing hands with soap.